Digital Contact Tracing for Pandemic Response Ethics and Governance Guidance - Kahn, Jeffrey P.; Johns Hopkins University. Johns Hopkins Project on Ethics and Governance of Digital Contact Tracing Technologies; Johns Hopkins University; Project Muse.; Project Muse. (2020)
"Digital Contact Tracing Technology and closely related digital health products (together DCTT) have been used in several countries as part of broader disease surveillance and containment strategies. Globally, many digital COVID-19 contact tracing strategies have already emerged in response to the pandemic. In the U.S., DCTT has been proposed as an integral part of some plans to "reopen" the country (Allen et al. 2020; Hart et al. 2020; Simpson and Conner 2020). It is almost certain that these and related technologies will become part of not only the COVID-19 response, but also the wider toolbox for future public health communicable disease prevention and control." - from introduction.
Table of Contents
Open Access
Includes bibliographic references.
Description based on print version record.
Keywords: Cell phones; Medical technology; Pandemics -- prevention & control; Digital Contact Tracing Technology; Contact Tracing; Medical ethics; Public health; Medical policy; Coronavirus infections; COVID-19 (Disease); Electronic books; Electronic books